Electron temperature critical gradient and transport stiffness in DIII-D. (6th July 2015) - Smith, S.P.; Petty, C.C.; White, A.E.; Holland, C.; Bravenec, R.; Austin, M.E.; Zeng, L.; Meneghini, O.
Abstract: In a continuing effort to validate turbulent transport models, the electron energy flux has been probed as a function of electron temperature gradient on the DIII-D tokamak. In the scan of gradient, a critical electron temperature gradient has been found in the electron heat fluxes and stiffness at various radii in L-mode plasmas. The TGLF reduced turbulent transport model (Staebler et al 2007 Phys. Plasmas 14 055909) and full gyrokinetic GYRO model (Candy and Waltz 2003 J. Comput. Phys . 186 545) recover the general trend of increasing electron energy flux with increasing electron temperature gradient scale length, but they do not predict the absolute level of transport at all radii and gradients. Comparing the experimental observations of incremental (heat pulse) diffusivity and stiffness to the models' reveals that TGLF reproduces the trends in increasing diffusivity and stiffness with increasing electron temperature gradient scale length with a critical gradient behavior. The critical gradient of TGLF is found to have a dependence on q 95, contrary to the independence of the experimental critical gradient from q 95 .